2020
DOI: 10.3390/educsci10120386
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vocational Maturity in University Students with Disabilities to Access, Obtain an Internship and Complete University Studies

Abstract: In recent years, there has been a considerable increase in the number of university students with disabilities in Spain, as in other countries. Access to and completion of studies in higher education has been identified as a factor that improves the educational and labor inclusion of these people. However, this group of students faces difficulties in completing their studies, as they encounter problems in carrying out their internships, which is an obligatory element of many degrees. Our quantitative research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…SWD reported that SLC helped them develop self-advocacy skills, meet other SWD with STEM interests, gain disability awareness, as well as learning disclosure/accommodations and resume building. In Espada-Chavarria et al (2020)’s quasi-experimental study, SWD interested in internship experience were enrolled in the tutoring project, where they received training, information, and practical activities. SWD’s vocational maturity and generic competencies significantly increased after the training program.…”
Section: Resultsmentioning
confidence: 99%
“…SWD reported that SLC helped them develop self-advocacy skills, meet other SWD with STEM interests, gain disability awareness, as well as learning disclosure/accommodations and resume building. In Espada-Chavarria et al (2020)’s quasi-experimental study, SWD interested in internship experience were enrolled in the tutoring project, where they received training, information, and practical activities. SWD’s vocational maturity and generic competencies significantly increased after the training program.…”
Section: Resultsmentioning
confidence: 99%
“…National (Bocci, Cajola and Zucca, 2020;Pace, Pavone and Petrini, 2018;Pavone, 2017;D'Alonzo and Carruba, 2016;Caldin, 2017;CNUDD, 2014) and international studies (Espada-Chavarria, Moreno-Rodriguez, and Jenaro, 2020;Buckley, 2019;Briel and Getzel, 2001) however highlight some critical issues related to the conduct of curricular and extracurricular internships by students with disabilities and SLDs at university.…”
Section: The Debate On Internship and Disabilitymentioning
confidence: 99%
“…Studies such as [27] show how, based on university programs that promote the development of vocational maturity, higher rates of employability are achieved, resulting in a greater probability of gaining access to a job or an internship in a company. Both the capacity to look for a job or an internship and the capacity to obtain them, are factors that can be measured as indicators of the relevant level of professional maturity for employment.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasise this aspect given that the degree of vocational maturity has been related to the work success achieved [31]. Therefore, a person with high levels of vocational maturity may have more opportunities to obtain and maintain a job [27].…”
Section: Introductionmentioning
confidence: 99%